Developing an approach for teaching and learning about Lewis structures. Issue 12 (13th August 2017) - Kaufmann, Ilana; Hamza, Karim M.; Rundgren, Carl-Johan; Eriksson, Lars
ABSTRACT: This study explores first-year university students' reasoning as they learn to draw Lewis structures. We also present a theoretical account of the formal procedure commonly taught for drawing these structures. Students' discussions during problem-solving activities were video recorded and detailed analyses of the discussions were made through the use of practical epistemology analysis (PEA). Our results show that the formal procedure was central for drawing Lewis structures, but its use varied depending on situational aspects. Commonly, the use of individual steps of the formal procedure was contingent on experiences of chemical structures, and other information such as the characteristics of the problem given. The analysis revealed a number of patterns in how students constructed, checked and modified the structure in relation to the formal procedure and the situational aspects. We suggest that explicitly teaching the formal procedure as a process of constructing, checking and modifying might be helpful for students learning to draw Lewis structures. By doing so, the students may learn to check the accuracy of the generated structure not only in relation to the octet rule and formal charge, but also to other experiences that are not explicitly included in the formal procedure.